2009
DOI: 10.1002/jlcr.1593
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of deuterium labelled atropine and scopolamine

Abstract: Easy preparative scale syntheses of deuterium labelled atropine and scopolamine are described. [ 2 H 3 ]-atropine and [ 2 H 3 ]-scopolamine are obtained in good yield and good isotopic purity in two steps starting from the unlabelled alkaloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…1,7 Despite the importance of selective N-demethylation of tropane alkaloids, it has remained a challenging step for synthetic chemists. 8 Different approaches have been reported for N-demethylation of the tertiary amine in atropine and scopolamine using agents such as 2,2,2-trichloroethyl chloroformate, 9 α-chloroethyl chloroformate, 10 KMnO 4 10,11 and photochemistry. 12 Although these methods provide low to excellent yields (16-100%) of 5 and 8, they use toxic solvents and chemicals producing hazardous waste and by-products.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 Despite the importance of selective N-demethylation of tropane alkaloids, it has remained a challenging step for synthetic chemists. 8 Different approaches have been reported for N-demethylation of the tertiary amine in atropine and scopolamine using agents such as 2,2,2-trichloroethyl chloroformate, 9 α-chloroethyl chloroformate, 10 KMnO 4 10,11 and photochemistry. 12 Although these methods provide low to excellent yields (16-100%) of 5 and 8, they use toxic solvents and chemicals producing hazardous waste and by-products.…”
Section: Introductionmentioning
confidence: 99%
“…This investigation has further documented the oxidative Ndemethylation of atropine (1) and the opioids, thebaine (5) and oxycodone (8a), using the Fe III -TAML catalyst 15 and various different reaction conditions. On the basis of reactivity studies, it can be concluded that the 15-catalysed N-demethylation of atropine (1) to noratropine (13) with H 2 O 2 follows a biomimetic oxidation pathway involving formation of the N-hydroxymethyl-noratropine (21) intermediate.…”
Section: Discussionmentioning
confidence: 94%
“…Here, we report further studies designed to delineate the reaction pathway of the 15-catalysed N-demethylation of 1 and the impact of various parameters on the reaction selectivity and conversion efficiency. The reactivity of the opiate alkaloids thebaine (5) and oxycodone (8a) with the 15/H 2 O 2 system has also been documented, demonstrating that N-demethylation also occurs with these compounds, but with a reduced level of selectivity under the same conditions optimised for the tropane alkaloids.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations